The Marine Isotope Stage 12 pollen record from Lake Ohrid (SE Europe): Investigating short-term climate change under extreme glacial conditions - Koutsodendris, Andreas; Kousis, Ilias; Peyron, Odile; Wagner, Bernd; Pross, Jörg (Quaternary science reviews, 2019)
Characterised by a maximum expansion of continental ice sheets in the Northern Hemisphere, Marine Isotope Stage (MIS) 12 (∼478–424 ka before present) was one of the strongest glacials of the Quaternary. Because the information currently available on MIS 12 is predominantly derived from marine records, the imprint of this extreme glaciation on the terrestrial realm – and notably on terrestrial ecosystems – has remained poorly constrained. Here we present a new, centennial-scale-resolution pollen record from Lake Ohrid (Balkan Peninsula, SE Europe) augmented by pollen-based quantitative temperature and precipitation estimates. Our dataset, which spans the period from 488 to 420 ka, shows that the forest cover around Lake Ohrid decreased substantially over the course of MIS 12; this decrease was associated with a gradual lowering of winter and mean annual temperatures (and to a lesser extent of summer temperatures) as well as mean annual precipitation. Superimposed on this long-term development, abrupt changes in regional forest cover indicate a pronounced millennial-scale climate variability that bears strong resemblance to the interstadial and stadial events of the Last Glacial. This variability is expressed by repeated high-amplitude forest expansions and contractions around Lake Ohrid during MIS 12c and the oldest part of 12b substage (i.e., from ∼477 to 448 ka). The forest oscillations can be correlated to previously documented episodes of surface-water variability and ice-rafted debris deposition in the North Atlantic. This pattern suggests a coupling between the climatically forced tree-population changes in SE Europe and the variability of the Atlantic Meridional Ocean Circulation during MIS 12c and partially 12b on millennial timescales. In contrast, the youngest part of MIS 12b and MIS 12a (i.e., from ∼448 to 424 ka) lack high-amplitude forest expansions and contractions around Lake Ohrid. Comparison with sea-level reconstructions for MIS 12 suggests that millennial-scale vegetation variability in Lake Ohrid was strongest when sea level was between 30 and 100m lower than today, whereas it was absent when sea level was lower than 100m relative to the present.